PM2.5 Exposure and Health Symptoms in Elderly Residents: A Case Study in Jakarta during the COVID-19 Pandemic - Qonitan, Fatimah Dinan; Hilmi, Farhan M; Sarwono, Ariyanti; Ulhasanah, Nova; Wijaya, Angga Eka (Journal of Earth and Marine Technology (JEMT), 2024)
The deterioration of air quality in Jakarta, Indonesia, has become a growing public concern. Exposure to polluted air is known to be hazardous to public health, particularly for sensitive groups such as elderly citizens. PM2.5 (fine particulate matter with an aerodynamic diameter 2.5 μm) is among the most dangerous pollutants commonly found in urban atmospheres. This study assessed the relationship between atmospheric PM2.5 exposure and health-related symptoms among elderly citizens living in Jakarta, Indonesia. PM2.5 concentrations in ambient air were measured using a High Volume Air Sampler with a PM2.5 size-selective inlet for a week in an outdoor location at a nursing home during the Covid-19 pandemic. Health-related symptoms of elderly citizens were collected using a systematic interview method. Both sets of data were collected simultaneously for cross-sectional analysis. Based on the sampling data, PM2.5 concentrations in the area ranged from 15.4 to 42.9 μg/Nm3 (at standard conditions); the Air Pollution Standard Index ranged from 49.9 to 84.3; and the Air Quality Index was moderate for 6 out of 7 (85.7%) days. Results showed that sensitive groups, including elderly citizens, are very likely to be negatively affected by polluted air. The chi-square test results imply that emerging health-related symptoms are significantly affected by elderly citizen characteristics, such as age, gender, smoking habit, and residence time, rather than by the Air Quality Index.